Examining English Proficiency of Hotel Management Students: Study at Horison Hotel School - Rahmani, Sofia F; Laratmase, Antonia Junianty (English Language in Focus (ELIF), 2024)
This study aimed to measure the English proficiency of hotel management students and to analyze the factors that influence these abilities. The research method used was qualitative. The sample for this research was hotel management students from Horison Hotel School. Data was collected through English proficiency tests, observations, and interviews. The research results showed that many students had adequate English proficiency, although there are still several areas that need improvement, especially in speaking and writing skills. Factors that influence English proficiency include learning resources and access, learning motivation, and time in practicing English skills. The implication of this research was the need to develop learning strategies that are more effective and relevant to the needs of hotel management students, as well as increasing support and resources to improve their English proficiency. This study made an important contribution to the development of higher education and the hotel industry in preparing students to face global challenges.